The Vision of the Solitary Man - Mukhopadhyay, Nirmalya (Poetry of Bengal Ser., 2021)
The poems of Nirmalya are noteworthy for their grave, serious tone, for their architectonic beauty and harmony, for their love for the meditative solitariness of nature bordering on a pagan religiosity. The poem "Nature", a gem, a rare spark of Oriental genius; Nirmalya has absorbed almost the entire history of Bengali devotional literature into this masterpiece of linguistic art.